2021
DOI: 10.1186/s13104-021-05756-9
|View full text |Cite
|
Sign up to set email alerts
|

Application of bacteriophage as food preservative to control enteropathogenic Escherichia coli (EPEC)

Abstract: Objectives This study was conducted to characterize lytic bacteriophages infecting enteropathogenic Escherichia coli (EPEC) on several types of food and analyze their ability as phage biocontrol to be used as a food preservative. Characterization was done for bacteriophage morphology and stability, along with the determination of minimum multiplicity of infection (miMOI), and application of bacteriophage in the food matrix. Results Out of the five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Since the administration of phages directly to live animals until to ready-to-eat food, the biotechnological applications achieved using bacteriophages are diverse and still growing. Beyond the applications targeted in the food industry, bacteriophages are also widely studied and applied in areas such as health and sanitary treatment [ 108 , 109 , 110 , 111 , 112 , 113 , 114 ].…”
Section: Biotechnological Applicationsmentioning
confidence: 99%
“…Since the administration of phages directly to live animals until to ready-to-eat food, the biotechnological applications achieved using bacteriophages are diverse and still growing. Beyond the applications targeted in the food industry, bacteriophages are also widely studied and applied in areas such as health and sanitary treatment [ 108 , 109 , 110 , 111 , 112 , 113 , 114 ].…”
Section: Biotechnological Applicationsmentioning
confidence: 99%
“…Studies have shown that genetically modifying phages for increased enzyme production and biofilm penetration increases phage activity. Genetically modified (GM) T7 E. coli phage for example expresses intracellular hydrolase which is released into the EPS matrix promoting biofilm degradation achieving a 99% elimination of biofilms [ 72 , 73 ]. Phages may also encode extracellular polysaccharides (EPS) depolymerases, enzymes allowing for increased biofilm penetration [ 70 ].…”
Section: Bacteriophages and Food Productionmentioning
confidence: 99%
“…The application of phages as biocontrol agents in foods is influenced by many factors, including the food matrix, surface area, structure, bacterial species and load, inhibitory compounds and dose of phage applied [ 73 ] ( Table 2 ). Due to the nucleic acid content of phage’s however, temperature, water content and the presence of chemicals are also likely to impact on phage stability and activity [ 39 ].…”
Section: Industrial Application Considerationsmentioning
confidence: 99%
“…In the past decade, scientists reported the isolation of diverse phages in SEA from different sample types, with potential activities against human pathogens (Table 2). Among the phages discovered in the region with notable activity against MDR organisms are: (1) phages vB_AbaM_PhT2 (Styles et al, 2020) and AB1801 (Wintachai et al, 2019), which exhibited anti-MDR A. baumannii activity, in vitro and in vivo, respectively, (2) phage UPM2146 (Assafiri et al, 2021), which exhibited activity against carbapenem-resistant K. pneumoniae, in vitro and in vivo, (3) phage C34 (Guang- Han et al, 2016), which controlled naturally resistant Burkholderia pseudomallei bacterial load, in vivo, (4) phage ΦHN10 (Phothichaisri et al, 2018), which exhibited the highest breadth of activity against various Clostridiodes difficile strains, in vitro, (5) phage ΦKAZ14 (Ahmad et al, 2015), which induced lysis of extended-spectrum betalactamase (ESBL)-producing Escherichia coli, in vitro, (6) phages UPMK_1 and 2 (Dakheel et al, 2019) and ΦNUSA-1 and 10 (Tan et al, 2020), which all exhibited lytic activity against methicillin-resistant Staphylococcus aureus (MRSA), and antibiofilm activity for the first two phages in in vitro experiments, (7) cocktail of phages vB_SenS_WP109, WP110, and WP128 (Pelyuntha et al, 2021), which induced lysis of multiple MDR Salmonella serovars, in vitro, and (8) phages KP1, 2 Poultry and farm feces, urban catchment, tissue samples Indonesia, Malaysia, Singapore Lau et al, 2012;Gan et al, 2013;Rezaeinejad et al, 2014;Ahmad et al, 2015;Vergara et al, 2015;Sellvam et al, 2018;Lukman et al, 2020;Dewanggana et al, 2021;Sjahriani et al, 2021;Waturangi et al…”
Section: Phages In Seamentioning
confidence: 99%